Anatomical changes in stem and root of soybean plants submitted to salt stress - Silva, B. R. S.; Batista, B. L.; Lobato, A. K. S.; Luo, Z.‐B. (Plant biology (Stuttgart, Germany), 2021)
The soybean is a legume that is widely cultivated in many countries due to the high levels of protein and oil contained in its seed, and is used for human and animal nutrition. However, salinity affects more than 800 million hectares worldwide, limiting global agricultural production. The aim of this research was to evaluate the structural behaviour of the roots and stems under progressive salt stress, detailing the possible anatomical modifications to these organs in soybean plants during this stress. The plants were randomized into five treatments (0, 50, 100, 150 and 200 mm NaCl). All the root regions studied and exposed to 100 mm Na+ exhibited increases in the epidermis and endodermis and formation of lysogenic aerenchyma with increasing salinity, revealing the protective roles of these structures in reducing Na+ influx. In the stem, increases in the cortex and pith in the first internode subject to 100 mm Na+ suggest anatomical responses that aim to minimize oxidative stress. Soybean plants subjected to progressive salt stress (>50 mm Na+) avoided cavitation and loss of function linked to vessel elements, reducing the metaxylem in all the root and stem regions analysed. Finally, our results confirm anatomical changes to the roots and stems. Soybean plants subjected to progressive salt stress exhibited anatomical modifications in root and stem tissues to minimize the deleterious effects associated with Na+.